Estudo da atividade anestésica local de um fator isolado do veneno do Bufo paracnemis na polpa dentária de coelho - Freitas, Solane Fernandes (2001)
Amphibian skin has a lot of vital functions. It is responsible for the production of a lot of substances, with several pharmacological effects, such as biogenic amines, alcaloids, steroids, proteins and peptides. In this study, it was isolated from the parotoid glands of Bufo paracnemis a factor with potent local anesthetic activity. The venom extract was dissolved in ethanol (100%) and it was kept overnight at 4°C overnight. The mixture was centrifugated at 5000 g and the pellet was descarded. The supernatant was fractionated by High Performance Liquid Chromatography (HPLC) using a isocratic sistem with acetonitrile at 40%. The peak that presented local anesthetic activity was used in pharmacological studies of tooth pulp stimulation. The molecular weight of the factor is 402 Da. Its parcial structure seems at steroids group of the bufogenin family. DL50 by intravenous administration in mice of the factor (30 mg/kg) is greater than that of lidocaine (18.8 mg/ kg) and that of bupivacaine (7.9 mg/kg), showing smaller agude toxicity. In tooth pulp stimulation test, the factor in the concentration of 0.25% and 0.5% presented greater potency than bupivacaine. Furthermore, it also presented the same anesthetic durabiliy than that of bupivacaine in same concentrations. The factor in concentrations of 0.25% and 0.5% showed greater potency and durability of action than lidocaine in concentrations of 1% and 2%, respectively. This substance may represent act as an important scientific tool to research a new local anesthetic class for clinicai use in dentistry.